Proyecto de inversión para la creación de un mercado municipal en el GAD parroquial, de la Esperanza, año 2015 - Molina Caicedo, Kerly Isaura (2016)
The research work was located in the parish of La Esperanza, Canton Quevedo, and Los Rios Province. This information is well organized with major to investigate that were formalized the investment plan for the creation of a municipal market as it is necessary for the complete change of informal traders goals. The research identifies the problematic sites for the Municipal Market primary purpose is to overcome the barriers to their full entity with society, such as poor health, lack of organization and conditions that both the client and the informal trader exposed. In addition to the analytical methodology allowed analyze the causes and effects that exist in the various drawbacks in Marroquin La Esperanza, all this was made possible through a systematic process the same hosting different methods for the preparation of this research. All research techniques were obtained as results favorable gathering information for this project. So to learn the concepts and theories define, especially the theoretical, conceptual and referential basis, in order to have all the knowledge to my development effectiveness research. And finally the probability sampling, which underlay to establish the size of the sample survey residents and informal traders Parish La Esperanza was applied, the market research that led results related to the creation was also developed, the study demonstrates technical infrastructure and organization, financial aspects was necessary to operate the investment for such work, corporate identity finally closing the documentary proposal exposed. It ended with conclusions and recommendations. Keywords: City market. Investment plan. Informal commerce.